A rare isolated cutaneous metastatic mass after colon cancer resection. Issue 12 (30th December 2021) - Fong, Suysen Hung; Narasimha, Neethi; Thakkar, Rishabh; Misra, Subhasis; Thakkar, Darshan
Abstract: Metastatic cutaneous lesions from colorectal in origin are extremely rare, and especially without any visceral metastasis. Due to its poor response to chemotherapy, it is a poor prognostic indicator with a 1–6 month(s) death rate. Routine screening colonoscopy should be highly encouraged. This case is about a patient with obstructing, bleeding right colon mass and metastatic cutaneous soft tissue mass postcolonic mass resection. The biology and the mechanism of these metastatic lesions are not well understood, and they can be mistaken with any other primary soft tissue malignancy.